In vitro Complexation of Olmesartan Medoxomil with Dapagliflozin, Vildagliptin and Metformin - Aktar, Fahima; Sultan, Md Zakir; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Drug-drug interactions have been a serious concern for pharmacokinetics, pharmacodynamics and pharmacological profiles of therapeutic agents. The aim of this study was to carry out interactions of olmesartan medoxomil with dapagliflozin, vildagliptin and metformin, which were confirmed by TLC, HPLC and FT-IR. The newly formed complexes showed characteristic thermochemical properties in differential scanning calorimetry (DSC) and thermo gravimetric analysis (TGA). In TLC, three spots from the three complexes were found to be different from their precursor drugs. In HPLC chromatograms, the Rt (retention time) of the pure olmesartan medoxomil, dapagliflozin, vildagliptin and metformin were found to be different from their respective complexes. The FT-IR spectra obtained for drug-drug interactions were seen to demonstrate new pattern of peaks compared to pure drugs. The DSC and TGA thermograms of olmesartan medoxomil, dapagliflozin, vildagliptin and metformin were also found to be different from their complexes. All these variations from parent compounds indicated the formation of new complexes. Dhaka Univ. J. Pharm. Sci. 18(2): 271-180, 2019 (December)